2010
DOI: 10.1002/app.32750
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and properties of high performance PEEK/Si3N4 nanocomposites

Abstract: The crystallization, morphology, microhardness, scratch hardness, dynamic modulus, and wear behavior of high performance poly(ether-ether-ketone) (PEEK) matrix nanocomposites reinforced with 0 to 30 wt % silicon nitride (Si 3 N 4 ) nanoparticles were reported. The crystallinity of PEEK nanocomposites increases at 2.5 wt % Si 3 N 4 but, thereafter it decreases with increasing Si 3 N 4 content due to the hindrance to the ordering of PEEK chains. The crystallization peak temperature and crystallization onset temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 22 publications
1
19
0
Order By: Relevance
“…This is due to slow heating rate (3°C/min) used in this study in contrast to the reported one (5°C/min), which causes higher expansion to matrix in a given time. Second, weak reduction in CTE with increasing Si 3 N 4 content may be attributed to decreasing crystallinity of PEEK fraction in nanocomposites as confirmed from XRD and differential scanning calorimetry [28]. Nevertheless, it is interesting to note that the commercial Polyclad's product PCL‐FR‐226/240 laminate (epoxy/E‐glass) exhibits CTE of 50 × 10 −6 /°C.…”
Section: Resultsmentioning
confidence: 99%
“…This is due to slow heating rate (3°C/min) used in this study in contrast to the reported one (5°C/min), which causes higher expansion to matrix in a given time. Second, weak reduction in CTE with increasing Si 3 N 4 content may be attributed to decreasing crystallinity of PEEK fraction in nanocomposites as confirmed from XRD and differential scanning calorimetry [28]. Nevertheless, it is interesting to note that the commercial Polyclad's product PCL‐FR‐226/240 laminate (epoxy/E‐glass) exhibits CTE of 50 × 10 −6 /°C.…”
Section: Resultsmentioning
confidence: 99%
“…One prominent group comprises the carbon fiber reinforced PEEK (CFR PEEK) composites, which are already known for a long time due to their versatility, compatibility with modern imaging technologies, adjustable mechanical properties, and biocompatibility . Other potential composites with PEEK include carbon nanotubes (CNTs); TiO 2 ‐; ZrO 2 ‐; Al 2 O 3 ‐; Si 3 N 4 ‐; ZnO‐; SiO 2 ‐; SiC‐; calcium silicate nanoparticles; bioglass; combinations of soft‐hard nanoparticles, such as Bi 2 O 3 ‐SiO 2 , CuO‐SiO 2 , or WS 2 ‐SiC; polymer blends; or mixtures of the aforementioned . These composite materials did not only demonstrate significantly improved mechanical properties but also a better in vitro biocompatibility when compared to pure PEEK.…”
Section: General Strategies To Improve the Bioactivity Of Peekmentioning
confidence: 99%
“…Even though polymer composites reinforced with ceramic materials 11, 18 have been studied 4 early, with the practical requirement, it is necessary to develop such an investigation on tribological properties of polymer (especially PI) mated with ceramic materials. Besides, due to the application of bearing of polymer in industry, it is necessary to study the tribological properties of PI-ceramic pairs.…”
Section: Introductionmentioning
confidence: 99%